Study of Service Quality, Product Quality, Price Perception, Trust, and Brand Image of IDX Data Service Product Purchase Decisions - Dio Tutut Kusuma Wardani; Harry Soesanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to examine and analyze the effect of service quality, product quality, price perception, trustworthiness, and brand image on the purchasing decisions of IDX data service products. The approach used in this research is a quantitative approach. The research data is primary data obtained from a sample of 122 customers or IDX Data Service Product license recipients as respondents. Respondents were asked to provide an assessment/percept-ion of the variables of service quality, product quality, price perception, trustworthiness, brand image, and purchasing decisions of IDX data service products. The data were analyzed using the Structural Equation Model (SEM) analysis technique using the AMOS (Analysis of Moment Structure). The results showed that service quality and product quality had no significant effect on brand image. Meanwhile, price perception and trust have a significant and positive effect on brand image. The results of the analysis also show that brand image has a significant and positive effect on purchasing decisions for IDX data service products.